Podobe starosti v slikarstvu Ivane Kobilca - Vignjević, Tomislav (Acta historiae artis Slovenica, 2024)
The painter Ivana Kobilca created a series of paintings and studies on the theme of old age, so that more than twenty-five of her works depicting the elderly have survived. This is an important segment of the artist’s oeuvre, which testifies to her lively interest in images of the elderly. These images in her paintings can most often be characterised in terms of genre as character studies of the head or bust, where the painter displayes a characteristic and very pronounced realistic tendency towards a detailed, and one might say psychologically profound, study of the physiognomies of the elderly. Her interest, in short, goes beyond the initiation in this genre that she received during her studies in Munich and testifies to her sensitivity to the motifs of old age
Keywords: 19. stoletje; 19th century; Ivana Kobilica; Kobilca, Ivana; old age; painting; realism; realizem; Slikarstvo; starost